‘Vocales,’ or Early Nominalists - Yukio, Iwakuma (Traditio, 1992)
In Section 1 of the present essay I present evidence that in the early twelfth-century nominalists were called vocales, a name that only later was replaced by nominales. In Section 2 I argue that ‘vocalism' arose about 1080, one generation of scholars before Roscelin. Since Garlandus' vocalistic Dialectica could be thought to provide evidence of an even earlier origin of the theory, Section 3 will deal with the date of this work, which has wrongly been assigned to the mid-eleventh century or earlier. Sections 4–6 will present a number of unpublished texts by vocalist authors, and the Appendix will supply editions of vocalist texts commenting on or otherwise discussing Porphyry's Isagoge.